Regional Specifics of Municipal Solid Waste Management in Arctic Regions of the Russian Federation - Elena V. NEDOSEKA; Vladimir V. KOZLOVSKIY (Arctic and North, 2021)
The article analyzes the regional specifics of solid municipal waste management in the Arctic zone of the Russian Federation. The relevance of the topic is determined by the need to analyze the regional specifics of solid municipal waste management within the framework of the federal project "Integrated System of Solid Municipal Waste Management", included in the national project "Ecology". First of all, this request will allow us to achieve the most effective management decisions in the field of regulatory regulation and the introduction of mechanisms for economic regulation of MSW management activities, as well as to contribute the creation of an effective management system, and the development of infrastructure for MSW management. The statistical analysis of formation indicators, processing and utilization of MSW waste in the structure by region is presented in this paper. The factors determining the specificity of MSW handling in the Arctic regions are defined. The expert survey made it possible to identify the main problems of implementing the garbage reform in the Arctic in general and in inner regions in particular. The main methods in this study were: semi-formal telephone interviews with representatives of environmental organizations and associations (18 informants), as well as collecting and analysis of statistical indicators of the MSW handling in the Arctic regions.